PERSEPSI NILAI DAN KUALITAS HUBUNGAN TERHADAP CCB DENGAN MEDIASI KEPUASAN PELANGGAN PADA TRANSPORTASI ONLINE GRAB DI SURABAYA - Aisy, Aribah Rihadatul (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2019)
This study was aimed to determine The Effect Of Perceived Value and Relationship Quality Towards Customer Citizenship Behavior (CCB) to Online Transportation Grab in Surabaya: With Satisfaction as an Intervening Variable. The samples of this study is 200 people who used Grab in Surabaya and collecting data was conduct by a questionaire distributed directly to the respondent. Sample were analyzed by purposive sampling technique with non probability sampling methods. The statistical method used PLS followed by software WarpPLS. The result of this study showed that Customer satisfaction partially influences mediation on the relationship quality with Customer Citizenship Behavior (CCB). Furthermore, Customer satisfaction does not have a partial or overall mediating effect on the Perceived Value with Customer Citizenship Behavior (CCB). Key words: Perceived Value, Relationship Quality, Customer Citizenship Behavior (CCB), Grab